Stress Cardiac MRI in Women With Myocardial Infarction and Nonobstructive Coronary Artery Disease. Issue 10 (26th July 2016) - Mauricio, Rina; Srichai, Monvadi B.; Axel, Leon; Hochman, Judith S.; Reynolds, Harmony R.
Abstract : Background: In a prospective study, cardiac MRI (CMR) and intravascular ultrasound were performed in women with myocardial infarction (MI) and nonobstructive coronary artery disease (MINOCA). Forty participants underwent adenosine‐stress CMR (sCMR). Hypothesis: Abnormal perfusion may co‐localize with ischemic late gadolinium enhancement (LGE) and T2‐weighted signal hyperintensity (T2+), suggesting microvascular dysfunction contributed to MI. Methods: Qualitative perfusion analysis was performed by 2 independent readers. Abnormal myocardial perfusion reserve index (MPRI) was defined as global average ≤1.84. Results: Abnormal rest perfusion was present in 10 patients (25%) and stress perfusion abnormalities in 25 (63%). Abnormal stress perfusion was not associated with LGE but tended to occur with T2+. Among patients with abnormal perfusion and LGE, the LGE pattern was ischemic in half. The locations of abnormal perfusion and LGE matched in 75%, T2+ in 100%. Abnormal stress perfusion was not associated with plaque disruption and matched in location in 63%. MPRI was abnormal in 10 patients (25%) and was not associated with LGE, T2+ or plaque disruption. Conclusions: Abnormal perfusion on sCMR is common among women with MINOCA. Abnormal perfusion usually co‐localized with LGE and/or T2+ when present. Variability in LGE pattern leads to uncertainty about whether the finding of abnormal perfusion was cause or consequence of the tissue state leading to LGE. Low MPRI, possibly indicating diffuse microvascular disease, was observed with and without LGE and T2+. Multiple mechanisms may lead to abnormal perfusion on sCMR. Microvascular dysfunction may contribute to the pathogenesis of and coexist with other causes of MINOCA.